Mengoptimalisasikan Dampak Perbedaan Pendapat Masyarakat Akibat Kesalahpahaman Dari Bahasa Daerah - Tirta Naila; Syafitri Syafitri; Surya Deva; Nurul Hafiza; Winda Andini; Sari Rambah Andini (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This research aims to understand how to optimize the impact of misunderstandings. The study uses the literature review method by investigating 12 journal articles published between 2017 and 2024. The study aims to analyze the forms of misunderstandings in regional languages, as well as differences in public opinion in regional language, and the impact of their differences so as to find ways to optimize the misunderstanding of local languages. The results of this study showed some forms of misunderstanding in the use of regional languages, such as pronunciation, logarithm, and interregional tone of speech. In research, it was found that character differences in speech, such as a loud and fast tone, can increase the likelihood of misunderstanding when two people from different areas speak.